Effects of Dose Rate on the Reproductive Cell Death and Early Mitochondrial Membrane Potential in Different Human Epithelium-Derived Cells Exposed to Gamma Rays - Nguyen T. K. Vo PhD; Marwan Shahid BSc; Colin B. Seymour PhD; Carmel E. Mothersill PhD (SAGE Publishing, 2019)
Dose rate is one of the most varied experimental parameters in radiation biology research. In this study, effects of dose rates on the radiation responses of 2 different types of human epithelium-derived cells, immortalized keratinocytes (HaCaT), and colorectal cancer cells (HCT116 p53 +/+ and HCT116 p53 −/− ) were systematically studied. Cells were γ-irradiated at one of the 4 dose rates (24.6, 109, 564, and 1168 mGy/min) to a total dose of 0.5 to 2 Gy. Clonogenic survival and mitochondrial membrane potential (MMP) were measured to assess the levels of reproductive cell death and damage to mitochondrial physiology, respectively. It was found that clonogenic survival was similar at all 4 tested dose rates in the 3 cell lines. The loss of MMP occurred at all tested dose rates in all 3 cell lines except for one case where the MMP increased in HCT116 p53 +/+ cells after exposure to 0.5 Gy at 24.6 mGy/min. In HCT116 cells, the loss of MMP was the most severe at high dose/dose rate combination exposure and when p53 was expressed. In contrast, no effect in dose rate was observed with HaCaT cells as the reduction level of MMP was similar at the tested dose rates.